P416 Faecal calprotectin can predict mucosal healing in patients with inflammatory bowel diseases treated with vedolizumab: a prospective single-centre study. (25th January 2019) - Bertani, L; Ceccarelli, L; Mumolo, M G; Tedeschi, R; Albano, E; Tapete, G; Baiano Svizzero, G; De Bortoli, N; Ricchiuti, A; Bellini, M; Marchi, S; Costa, F
Abstract: Background: Vedolizumab (VDZ) is currently a good therapeutic option for ulcerative colitis (UC) and Crohn's disease (CD); nevertheless, according to real-life studies, despite a good effectiveness in terms of clinical response, only 40% of patients achieve Clinical Remission (CR), and even less Mucosal Healing (MH). There is little knowledge about early markers of therapeutic response, especially of MH. Methods: A prospective observational study was carried out among patients with moderate-to severe UC and CD who started VDZ between June 2016 and June 2017. Primary non responder were excluded. Partial Mayo Score (PMS) for UC and Harvey–Bradshaw Index (HBI) for CD, C-Reactive Protein (CRP) and faecal calprotectin (FC) were assessed before treatment, at Week 6 and every 8 weeks during the follow-up. All the patients underwent colonoscopy at baseline and at Week 54 or in case of discontinuation of therapy due to loss of response (LOR). We defined as MH a Mayo Endoscopic Score ≤ 1 for UC, and the absence of ulcerations for CD. All the colonoscopies were performed by a single blinded operator. Clinical remission (PMS<2 or HBI<5), a normal CRP value (<0.5 mg/dl), and the values of FC were evaluated as potential predictors of MH and CR at Week 54. Statistical analysis was carried out using ROC curves and Fisher's test as appropriate. Results: We enrolled 45 patients (31 UC and 14 CD). Thirteen (29%) patients (10 UC and 3 CD) experienced LOR. MH was reached in 18 patients (40%)—14 UC and 4 CD—whereas CR in 26 (58%)—17 UC and 9 CD. FC at Week 6 correlated with MH, and ROC curve analysis identified an AUC of 0.822 with a sensitivity of 82% and a specificity of 83% at the cut-off of 180.5 µg/g ( p < 0.001). The same results were observed for CR, where ROC curve identified an AUC of 0.739 with a sensitivity of 84% and a specificity of 69% at the cut-off of 195.5 µg/g ( p < 0.01). CR and CRP values at Week 6 showed no correlation with MH or CR at Week 54. Conclusions: Our results showed that an early drop of FC levels is a good predictor of MH and CR at 1 year in UC and CD patients treated with VDZ. FC assessment could represent a promising early marker of response to therapy, especially considering the slow onset of action of VDZ.